Memahami Dampak Penerapan Teknologi Informasi dan Komunikasi Terhadap Hasil Belajar Islam Santri di Era Digital - Abdul Walid; Andri Kurniawan; Raya Mangsi; Ida Farida; Sri Utami (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This article discusses the impact of information and communication technology on student learning outcomes, in which the influence of information technology cannot be avoided in students' lives. The study in this research is qualitative by using the literature method. Literature is taken from books, journals and others related to technological issues and student learning outcomes in the information age. The data obtained were analyzed and searched according to the problems in this study. The results of the study show that learning that utilizes digital applications can improve student learning outcomes. Because, the information technology used by students can broaden the scientific treasures of students to obtain information as desired by students from the subject matter taught by the teacher.